Analisis Dampak Pemotongan Anggaran Belanja pada Kinerja Badan Pengawasan Keuangan dan Pembangunan (BPKP) - Airin Mentari; Nurhidayat Nurhidayat; Siti Aisah Rahmah Wati; Zainal Umaaya (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study aims to determine the impact of the budget cuts on the performance of the Financial and Development Supervisory Agency. This research was carried out at Finance and Development Supervisory Agency Representatives of Riau because it is an echelon II unit that best represent the main business of Finance and Development Supervisory Agency, namely supervision of state/regional finance and national development. The study used a qualitative approach with case study design. Data collection was conducted through in-depth interviews with participants selected by purposive sampling and through document review. The results of this study indicate that the performance of Finance and Development Supervisory Agency Representatives of Riau was successful even though it was affected by budget cuts. This can happen because the Finance and Development Supervisory Agency Representatives of Riau has a method of implementing supervision, namely carrying out several assignments at the same locus at the same time